Participatory agro-climate information services: A key component in climate resilient agriculture - Simelton, Elisabeth; Beek, Robin aus der; Duong, Tuan M; Le, Tam T; Le, Hieu X; Madsen, Erik Junge; Nguyen, Yen T; Noorlander, Jan (2019)
The brief promotes participatory agro-climate information services as a key component in achieving climate-smart agriculture. The brief emphasizes that actionable agro-climate information starts with—and responds to—gender-based needs of farmers, integrated at all stages of the value chain. Timely forecasts and accurate agroclimate advisories have been proven to provide farmers with production, adaptation, and mitigation benefits.